Safety and Efficacy of a 6‐Month Placement of a Fully Covered Self‐Expanding Metallic Stent for Refractory Benign Biliary Stricture: A Multicenter Prospective Study - Tomohisa Iwai; Mitsuhiro Kida; Kazuya Sugimori; Hiroaki Shigoka; Takaaki Matsumoto; Masashi Ijima; Haruo Miwa; Kosuke Okuwaki; Masafumi Watanabe; Kai Adachi; Akihiro Tamaki; Taro Hanaoka; et al. (JGH Open)
ABSTRACT Background and Aim Managing benign biliary stricture endoscopically is complicated and challenging. This study aimed to evaluate the safety and efficacy of a 6‐month placement of a fully covered self‐expanding metallic stent for refractory benign biliary stricture. Methods Twenty‐two patients with refractory benign biliary stricture (13 with chronic pancreatitis and 9 without) were recruited from five higher tertiary care centers. All patients received a planned 6‐month fully covered self‐expanding metallic stent placement. Primary outcomes included clinical success, technical success of stent removal, adverse events, and stricture recurrence. Results Of the 21 cases (one case was excluded owing to malignant findings), fully covered self‐expanding metallic stent placement was successful in all cases, with contralateral bile duct plastic stents used in three patients and stents remaining in place for 6 months in 16 of 21 patients. Distal stent migration occurred in three cases, two of which had resolved strictures. Adverse events were observed in 19.0% of patients: one case of severe cholangitis, two cases of mild cholangitis, and one case of hyperplasia formation. No stent‐induced pancreatitis or cholecystitis occurred. All stents were removed successfully, and the treatment success rate was 85%. One patient experienced recurrent stricture 6.5 months post‐stent removal. Conclusions A six‐month placement of a modified fully covered self‐expanding metallic stent effectively improved strictures and minimized stent‐induced Adverse events in patients with refractory benign biliary stricture. Trial Registration UMIN ID: UMIN000025027